The effectiveness of the space allocated for advertising within cities (Al-Academy, 2024)
Advertisements have an important role in delivering information to the recipient, and there are several common ways to present these ads to them, including advertisements through communication sites, light advertisements, printed advertisements, and there are advertisements through internal or external roads, etc., in this research, the effectiveness of the allocated space will be clarified Within the cities, Baghdad (Al-Rusafa) is a model, as the importance of the advertisement lies not only in delivering the content of the advertising message to the recipients only, but in the way in which the content of the advertisement and the elements it contains influence the recipient in attracting and suspense, as it is considered the goal of the message for the advertised product It is the basis of the advertisement, so road advertisements are one of the printed advertisements through which they attract the attention of the recipient, and road advertisements are the most widespread in the streets of Baghdad because of their importance and effectiveness for the recipient, which is done through display and the location (the area in which the advertisements are placed) advertisement This is done in a vertical or horizontal way, so the promotion of goods and services that takes place through printed advertisements and how they are presented has an impact on the recipient, because advertisements are not limited to roads and include buildings, streets, malls and all areas of the recipient’s presence, as advertising is a means of influencing him, and later achieves the response that It is the ultimate goal of the advertisement, which represents the focus of the study for this research, so the research problem was identified by the following question:What is the effectiveness of advertising space within cities?